Rationalities in history: a Weberian essay in comparison - D'Avray, D. L. (Cambridge Univ. Press, 2010)
"In Rationalities in history, the distinguished historian David d'Avray writes a new comparative history in the spirit of Max Weber. In a strikingly original reassessment of seminal Weberian ideas, d'Avray applies value rationality to the comparative history of religion and the philosophy of law. Integrating theories of rational choice, anthropological reflections on relativism, and the recent philosophy of rationality with Weber's conceptual framework, d'Avray seeks to disengage 'rationalisation' from its enduring association with Western 'modernity.' This mode of analysis is contextualised through the examples of Buddhism, Imperial China, and sixteenth-century Catholicism--in the latter case building upon unpublished archival research. This ambitious synthesis of social theory and comparative history will engage social scientists and historians from advanced undergraduate level upwards, stimulating interdisciplinary discourse, and making a significant contribution to the methodology of history. D'Avray explores the potential of this new Weberian analysis further in his companion volume, Medieval religious rationalities"--Provided by publisher